Analysis of the Application of Muhammadiyah Values to Islamic Religious Education Students at Universitas Muhammadiyah Sumatera Utara - Maghfirah Chairunnisa; Indah Khairany; Zailani Zailani (UMSU, 2023)
The purpose of this study was to find out how far the application of Muhammadiyah values to Islamic Religious Education students at Universitas Muhammadiyah Sumatera Utara as a form of embodiment of the vision of the Islamic Religious Education study program in everyday life and the factors that influence it. Data collection techniques are in the form of observation, direct interviews and interviews in the form of questionnaires. The data analysis technique that was used is qualitative method. As for the values of Muhammadiyah are Aqidah, Akhlak, Ibadah and Muamalah Dunyawiyah. The implementation of Muhammadiyah values of UMSU Islamic Religious Education students is included in the category whether in the percentage of implementing the four Muhammadiyah values amounting to 68%. The factors that often become obstacles in the application of Muhammadiyah values in life are: 1. Internal factors, namely those related to determination, 2. External factors, which can be in the form of the community environment, association and family.